Legal regulation of labor of kazakh citizens abroad: use of international law and foreign legislation to improve the legislation of the Republic of Kazakhstan - Myktybayeva Д.А.; Davletgildeev Р.Ш. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2026)
Protecting Kazakhstan citizens seeking employment abroad is one of the key strategic objectives for the upcoming period, as defined in the Concept of Kazakhstan’s Migration Policy for 2023-2027. In this regard, this article attempts to examine international experience in legislatively regulating the departure of citizens to foreign countries for employment, as well as in regulating the requirements for drafting international treaties on this issue. The article aims to analyze international legal frameworks, including those of integration associations and national regulations on organizing the departure of citizens for employment, and to identify the minimum provisions of international treaties in foreign laws that cannot be deviated from when drafting and negotiating international treaties. This research suggests that the inclusion of minimum requirements for the content of bilateral international treaties in national legislation can increase the responsibility of countries of origin for migrant workers and ensure the completeness of international treaties, thereby enhancing the scientific and practical significance of this article. The article’s recommendations and conclusions can be used in developing amendments to national legislation in the area of international treaties and migration.